Effects of Hyperbaric and Decompression Stress on Blood Coagulation and Fibrinolysis: Comparison of Thromboelastography and Thromboelastometry. (May 2016) - Peng, Henry T.; Cameron, Bruce A.; Rhind, Shawn G.
Hyperbaric and decompression stress from diving impairs blood coagulation and fibrinolysis. We hypothesized that thromboelastography (TEG) and rotational thromboelastometry (ROTEM) were suitable to characterize the effects of stress on global hemostatic profiles. We thus conducted a comparative study of the hyperbaric effects on human coagulation using TEG and ROTEM. Maximum clot strength (maximum amplitude [MA]) and clot lysis (lysis index at time 30 minutes [LI30]) were reduced as indicated by TEG MA and EXTEM LI30, respectively. The relative changes in coagulation and fibrinolysis by the hyperbaric effects of diving were indicated by reduced TEG reaction time R at 5 hours, MA at 24 hours postdive, and reduced EXTEM coagulation time at 15 minutes postdive as well as decreased fibrinolysis (EXTEM LI30) at all postdiving time points investigated. Comparison of the parameter values and the diving-induced changes in each parameter between TEG and ROTEM showed both differences and correlations. The discrepancies between the 2 systems may be due to the different assay reagents used. Future studies will seek to further elucidate the changes in blood coagulation and fibrinolysis following varying levels of hyperbaric and decompression stress.